VIBRATION PROTECTION SYSTEMS WITH STIFFNESS CORRECTION - Архипов, Александр; Сухов, Виталий; Мариношенко, Александр; Козей, Ярослав (SWorldJournal, 2021)
Many technical facilities, especially mobile ones, operate under cyclic and shock loads. Safety and service life, optimal control of moving objects require the use of protective devices, the task of which is to reduce vibration and shock loads transmitte